Superconducting State of a Disk with a Pentagonal/Hexagonal Trench/Barrier - Barba-Ortega, J.; Gonzalez, J. D.; Sardella, Edson [UNESP] (Springer, 2014)
We study the influence of a pentagonal (hexagonal) trench or barrier on the superconducting properties of a perforated disk. Effects associated to the pinning (anti-pinning) force of the central hole and the trench (barrier) and the interplay between the boundary conditions and the shape of the inner defects on the vortex configuration are studied for a thin disk. Also, we considered two cases for the value of the order parameter at the surface. The first one is psi (s) not equal 0; this is the usual supercondutor/vacuum interface, for which the deGennes parameter is b -> a. The second one is psi (s) =0, which is the surface of the sample in a complete normal state, simulated by b=0. The vorticity, Gibbs free energy, magnetic induction, supercurrent density, magnetization and Cooper pairs density as a function of the external magnetic field are calculated. We show that in our sample new phenomena are possible due to the competing interactions of the boundary and the geometry of the sample and the added geometry of the nanoengineered trench and barrier.
Keywords: Ginzburg-Landau; Hexagonal trench; Pentagonal barrier; Mesoscopics